Penerapan Metode Jajah Alam Sekitar pada Pembelajaran Fisika Materi Fluida dalam Upaya Meningkatan Aktivitas Belajar Peserta Didik di SMA Negeri 2 Ungaran - Sri Indihartati (Jurnal Penelitian Pembelajaran Fisika, 2018)
The background of this reseacrh is that almost all the senior High shool student tuhnk that Physics is difficult subject, so the students don’t enjoy theaching leraning procesi in class. To solve the problem, the writer aplied “ Jelajah Alam Sekitar” method optimally. The purpose of this research is to apply “JAS” method in Fluida matery to know how it can improve to the student’s activities in teaching learning process in class. It is in Action Reserach which two cycles. The location is in SMA Negeri 2 Ungaran and the subject is the students of XI IPA6 grade 2016/2017. The writer get the data from the observatio sheet, discussion sheet and kognitif score. The improvment of the students activities can be seen at grafic of cycle 1 and 2. The students activities in preparing the equipments and materials improves 13 % and the antusiasm of teaching learning processi and group discussion improve 7 %. The experiment improves 6% and the presentation of the students discussion improve 5 %. The cognitive score improves 5,8%. Classical mastering improves 6 %. From that analysis we can conclude that the students activites and the score of the student in Physic speially in Fluida concept can be improve by applying JAS method.